Brother Odd - Koontz, Dean R. (Dean Ray), 1945- (New York : Random House Large Print, 2006)
St. Bartholomew's Abbey sits in majestic solitude amid the wild peaks of California's high Sierra, a haven for children otherwise abandoned, and a sanctuary for those seeking insight. Odd Thomas has come here to learn to live fully again. But trouble has a way of finding Odd Thomas, and it slinks back onto his path.
Keywords: Thomas, Odd (Fictitious character) -- Fiction; Mediums -- Fiction; Missing persons -- Fiction; Large type books; Suspense fiction